Symmetric Ram Migrations Style - Pirnazarov, Gulom Farhodovich; ogli, Khamdam Shavkat; Mukhammadiev (Procedia of Social Sciences and Humanities, 2022)
Symmetric Ram. Symmetric and inverse symmetric external loads. Calculation of symmetrical Ram by the method of displacement. To facilitate the calculation of symmetrical Ram by the method of displacement, it is necessary to introduce the method of grounding unknown, as well as the method of dividing external loads into symmetric and inverse symmetric loads.